Understanding molecular mechanisms of vertebral number of variations on Mongolian sheep using candidate genes analysis - Chimgee Purev; Huiguang Wu; Khosbayar Lkhagva; Odbayar Tumendemberel (Animal Bioscience)
Objective This study aimed to investigate the genetic link between variations in vertebral number and meat production traits, such as body weight and body measurements (body length, body height, heart girth, and shin width) in Mongolian (Bayantsagaan) sheep. Additionally, we examined the association of single-nucleotide polymorphisms (SNPs) in candidate genes, particularly vertnin (VRTN), nuclear receptor subfamily 6, group A, member 1 (NR6A1), and synapse differentiation-inducing 1-like (SYNDIG1L), with vertebral number variations and their potential impact on meat production traits. Methods The study involved 220 Bayantsagaan sheep from Bayantsagaan soum, Tov province, Mongolia, including 104 sheep with extra vertebrae group and 116 individuals with typical vertebral number as the control group. Morphological data, including body weight and body measurements, were collected, and genetic samples were obtained. The impact of vertebral number on morphological traits was estimated using a general linear model. The SNPs in the VRTN, NR6A1, and SYNDIG1L genes were sequenced, and their association with vertebral number was analyzed using one-way analysis of variance. Results Bayantsagaan sheep with extra vertebrae were, on average, 4.45 kg heavier and exhibited higher variability in body size traits compared to the control group. Four polymorphic sites were identified at the VRTN gene, with one polymorphic locus (VRTN1716) showing a significant association with vertebrae number and body size. Sheep with C/C genotype at VRTN1716 locus, had more vertebrae and larger body size compared to other genotypes. Conclusion The findings suggest that variations in vertebral number and VRTN gene polymorphisms are linked to favorable meat production traits in Bayantsagaan sheep. The identified SNP (VRTN1716) associated with vertebral number and body size offers the potential for marker-assisted selection in breeding programs. These results provide valuable insights into the genetic basis of meat production traits in Bayantsagaan sheep and may contribute to the development of more efficient breeding strategies.